The Relationship between Self-Efficacy and Diet Compliance in Diabetes Mellitus Patients at Jemursari Islamic Hospital, Surabaya: Hubungan Self efficacy dengan Kepatuhan Diet pada Pasien Diabetes Melitus di Rumah Sakit Islam Jemursari Surabaya - Fildzah Hendriawati; Difran Nobel Bistara; Khamida; Erika Martining Wardani; Susanti (Universitas Nahdlatul Ulama Surabaya, 2026)
Patients with diabetes mellitus frequently experience difficulties adhering to recommended dietary regimens, resulting in unstable blood glucose levels and an increased risk of further complications. One significant factor influencing dietary adherence is self-efficacy, or patients' belief in their own ability to manage their diet. This study aims to investigate the relationship between self-efficacy and dietary adherence among diabetes mellitus patients at Jemursari Islamic Hospital, Surabaya. This study employed a correlational analytical design with a cross-sectional approach. A total of 119 respondents were selected using a simple random sampling technique from a population of 170 patients with type 1 and type 2 diabetes mellitus. Data collection instruments included the Diabetes Management Self efficacy Scale (DMSES) for measuring self-efficacy and the Dietary Behaviour Questionnaire (DBQ) for assessing dietary adherence. Data were analyzed using Spearman's Rank correlation test. The results indicated that the majority of respondents had a low level of self-efficacy (fifty-three point eight percent) and moderate dietary adherence (forty-six point two percent). Statistical analysis revealed a significant positive relationship between self-efficacy and dietary adherence among diabetes mellitus patients (p = 0.000), with a strong correlation coefficient of 0.851. Based on these findings, self-efficacy was found to have a strong positive association with dietary adherence. Therefore, healthcare professionals are advised to emphasize simple and repetitive educational approaches, particularly targeting elderly patients with low to moderate educational levels, to enhance patients' confidence in consistently and independently adhering to diabetes dietary regimens. .